Latijnse renovatio van Byzantium. - Tricht, Filip van.
1 online resource.
Keywords: In 1204 the army of the Fourth Crusade sacked the great city of Constantinople. In earlier historiography the view prevailed that these Western barons and knights temporarily destroyed the Byzantine state and replaced it with a series of feudal states of their own making. Through a comprehensive rereading of better and lesser-known sources this book offers an alternative perspective arguing that the Latin rulers did not abolish, but very consciously wanted to continue the Eastern Empire. In this, the new imperial dynasty coming from Flanders-Hainaut played a pivotal role. Despite religious and other differences many Byzantines sided with the new regime and administrative practices at the different governmental levels were to a larger or lesser degree maintained.